Melatonin Bioavailability After Oral Administration of a New Delayed-Release Form in Healthy Male Volunteers - Samira Ait Abdellah; Caroline Gal; Isabelle Guinobert; Valérie Bardot; Véronique Raverot; Annarita Vitacca; Claude Blondeau; Bruno Claustrat (Adis, Springer Healthcare, 2024)
Abstract Background Two main types of galenic formulation, immediate release and prolonged release, have been developed to optimize melatonin bioavailability. We recently described the kinetic profile of a prolonged-release form generating a peak of plasma melatonin 1 h (T max) after intake, followed by a prolonged decay over time. We have developed a new oral form of melatonin with the aim of producing a melatonin peak several hours after intake. Objective The objective is to investigate melatonin bioavailability after administration of this new delayed-release form (DR form). Methods In this single-centre open-label study, 12 healthy male volunteers received one tablet of the DR form containing 1.9 mg melatonin, 10 mg zinc and 200 mg lemon balm extract (Melissa officinalis L aerial parts). Blood samples were collected for 12 h, beginning at 8:00 am. Plasma concentrations of melatonin and 6-sulfatoxymelatonin (6-SMT), the main hepatic melatonin metabolite, were determined by radioimmunoassay. Results A progressive increase in plasma melatonin concentrations was observed from 20 min and a peak about 3 h after intake (C max 740 ± 824 pg/mL; T max 179 ± 60 min). Concentrations remained high between 140 and 220 min, the concentration remaining physiologically significant (over 100 pg/mL) up to 7 h after intake. The DR form was well tolerated. Conclusions The melatonin release profile was consistent with what was anticipated for the DR form. The DR form generated a 2 h delayed T max compared with a prolonged-release form previously evaluated. This suggests that the DR form is suitable for the treatment of certain sleep disorders such as short sleep duration or early awakening. Trial Registry Registration number: NCT05419466.